Disaster Assistance Winners and Losers: Do Small Businesses Benefit?. Issue 3 (3rd July 2022) - Watson, Maria
Abstract: Problem, research strategy, and findings: Disaster assistance in the United States has faced criticism for widening the unequal impacts of disasters, but little is known about whether and how this phenomenon applies to businesses. Small businesses make up most businesses in the United States, but they are particularly vulnerable to hazards given their relative lack of capital. Because recovery assistance to businesses is primarily loan based, this lack of capital can create conflicts in how aid is perceived and allocated. Assistance providers must balance aiding the most severely damaged businesses and lending to those that will be able to repay; for small business, the threat of additional debt can make even low-interest loans seem risky. With this research I attempted to better understand how these competing factors play out in recovery through regression analyses of approved loan amounts and loan utilization decisions in Galveston (TX) after Hurricane Ike. I found that businesses with higher repayment ability such as larger businesses, older businesses, and corporations were approved for high loan amounts. Smaller businesses, businesses with higher damage, and businesses with longer loan terms were less likely to use the loans in their recovery, despite being approved. These findings suggest that businesses with the resources to recover were more likely to be the ones benefiting from additional disaster assistance. Takeaway for practice: These findings suggest that planners may need to create their own recovery programs specifically targeting subgroups of businesses that are important to their communities. Although important to many economic development initiatives, very small businesses, entrepreneurs, and sole proprietors may not benefit from federal assistance, particularly if they were severely damaged.